Navigating Legal Implications: The Impact of Enhanced Smartphone Integration on Security in Organizational Networks - Kenneth Ohei (Khazanah Hukum)
The escalating integration of smartphones within organizational frameworks has been driven by their augmented functionality, especially pertinent during the global pandemic. However, this surge in device utilization has concurrently amplified concerns surrounding security, as sensitive data becomes increasingly susceptible. In this context, the study conducted a survey to assess the security implications of smartphone integration while considering the legal aspects. The findings unequivocally substantiate the notion that smartphones pose substantial security risks, particularly when users stray from established protocols, potentially leading to legal consequences. Drawing from prior research emphasizing mobile devices' vulnerability, we advocate for a preemptive legal stance, suggesting the installation of anti-malware software on smartphones as a legally sound countermeasure. By doing so, organizations can thwart potential hacking endeavors, thereby not only fortifying network security but also mitigating legal liabilities and shielding sensitive information in compliance with relevant regulations. The implications of this study extend to organizational management and legal teams, enabling them to enact effective policies that reinforce network security and adhere to evolving legal challenges. This research underscores the significance of striking a balance between technological integration and safeguarding confidentiality within the boundaries of the law, offering essential insights for organizational resilience in an increasingly digitized landscape while avoiding legal pitfalls.